Evidence of ion energy distribution shift in HiPIMS plasmas with positive pulse. (22nd January 2019) - Avino, F; Sublet, A; Taborelli, M
Abstract: The deposition of a dense and void-free coating in complex geometries can be obtained with High Power Impulse Magnetron Sputtering (HiPIMS) by negatively biasing the substrate. This accelerates the incoming metal ions that consequently densify the film. However, a biased substrate can be a technical challenge for large objects that are generally kept grounded. HiPIMS with a positive voltage pulse after the main negative one is a potential alternative to be still fully investigated. In this letter, we report on the first measurements of a dominant population of energetic ions in HiPIMS with a positive pulse. Time-integrated energy distribution functions of the background gas ions (Ar + ) and target ions (Nb + ) are measured with and without the positive pulse. The peak of low energy ions at ∼2 eV is shown to disappear by varying the duration of a +50 V pulse. For a sufficiently long duration of 100 μ s, energy peaks in the range of ∼30 eV are observed for both Ar + and Nb + . Negligible ion fluxes at the energies below 10 eV are measured for 250 μ s, indicating an effective acceleration of ions towards the substrate. Time-resolved ion flux measurements provide insights on the positive pulse effect on the ion fluxes.